2002
DOI: 10.1002/ijpg.257
|View full text |Cite
|
Sign up to set email alerts
|

Professional and managerial migration from core to periphery: the case of English migration to Scottish cities

Abstract: The population of English-born persons living in Scotland has risen rapidly since 1971. The dynamics of the group are theorised in this paper relative to the escalator region hypothesis, in terms of the role of professional and managerial staff linking global cities with lower-order urban centres within their hinterland. A hierarchical log-linear modelling approach is taken in explaining the highly structured geography of English migration to Scotland's four largest urban centres. Links between place of birth,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
4

Year Published

2003
2003
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 14 publications
1
16
0
4
Order By: Relevance
“…Both groups of lifetime migrants are over-represented amongst the elite elements of London's population, with high levels of higher education, social class distributions that emphasise the higher-status groups, and residential patterns that generally accord with London's more affluent neighbourhoods. These findings are similar to those found in the investigation of English migrants in Scotland's cities (Findlay et al, 2002). The explanation may lie in the high relative" mobility of educated middle-class professional and service sector populations, who are prepared to take up the opportunities offered in any of the bigger cities of the UK.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Both groups of lifetime migrants are over-represented amongst the elite elements of London's population, with high levels of higher education, social class distributions that emphasise the higher-status groups, and residential patterns that generally accord with London's more affluent neighbourhoods. These findings are similar to those found in the investigation of English migrants in Scotland's cities (Findlay et al, 2002). The explanation may lie in the high relative" mobility of educated middle-class professional and service sector populations, who are prepared to take up the opportunities offered in any of the bigger cities of the UK.…”
Section: Discussionsupporting
confidence: 83%
“…The reverse movement of the English into Wales has been discussed by Giggs & Pattie (1992) who identified the particular strength of such migration and its impact on the population of the Principality, highlighting the role of the mobile service class. Recent work on the movement of the English into Scottish cities (Findlay et al, 2002) has emphasised the same group, and shown how (particularly in Edinburgh) the English-born are not just Downloaded by [The University of Manchester Library] at 09:28 03 December 2014 the largest migrant group but also one of the most distinctive in terms of residential concentration, neighbourhood characteristics, and labour market position. There have also been a number of recent studies of English migrants in rural Scotland (e.g.…”
Section: Migration To the Uk Capitalmentioning
confidence: 97%
See 1 more Smart Citation
“…Specific to the Mearns it is entirely plausible that at least some inmigrants have been displaced by rising house prices in nearby Aberdeen. Moreover, evidence from Findlay et al (2002) suggest that Scotland's cities -and especially Edinburgh -represent 'escalator regions' and accordingly are associated with significant professional and managerial inflows. Such inflows have undoubtedly affected urban property markets.…”
Section: The Migration Process and Gentrification Impactsmentioning
confidence: 98%
“…Lower-income migrant households, by comparison, relocated over shorter distances (for example, one in two moved within their current district of residence), and fewer inter-regional (36 percent) and England-Scotland (approximately 10 percent) moves were recorded. Previous research (Findlay et al, 2002;Short and Stockdale, 1999) has noted that migrants from England commonly relocate to Scotland's cities, and then participate in within Scotland migration flows to a rural destination. The fact that one in five potential gentrifiers moved directly from England (rising to 28 percent in Crieff and 24 percent in the Black Isle) suggests that gentrification of the Scottish countryside (defined in income terms) is associated with a strong anglicised influence.…”
Section: The Migration Process and Gentrification Impactsmentioning
confidence: 98%